2011
DOI: 10.1159/000327007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Survival in Stomach Cancer – Analysis of 15 Years of Data from a Referral Hospital in Iran and Evaluation of International Variation

Abstract: Background: Stomach cancer is the most common cancer among Iranian men. We studied survival rates and prognostic factors of stomach cancer in a referral hospital in Tehran, Iran. Patients and Methods: We followed 367 stomach cancer patients hospitalized between 1991 and 2007 in the Baqyiatallah Hospital. We estimated survival rates overall and among operable patients exclusively. Hazard ratios (HR) for the different prognostic factors were estimated with the Cox regression model. Furthermore, we studied intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Many studies have reported on the prognostic importance of several clinicopathological factors, such as age, gender, macroscopic type (Borrmann I, II, III, and IV), tumor size, cell differentiation and TNM classification (Gobbi et al, 2011;Jiang et al, 2011;Khedmat et al, 2011), therefore, the multivariate analysis which included the expressions of RARa, RARβ, RARγ, RXRa, RXRβ and RXRγ and the aforesaid clinical variables was performed using the Cox proportional hazards mode. The score of the expressions of RARs/RXRs from 1 to 3 calculated RARs/RXRs positive, while the score of the expression of RARs/RXRs zero calculated RARs/RXRs negative.…”
Section: Rna Expression Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported on the prognostic importance of several clinicopathological factors, such as age, gender, macroscopic type (Borrmann I, II, III, and IV), tumor size, cell differentiation and TNM classification (Gobbi et al, 2011;Jiang et al, 2011;Khedmat et al, 2011), therefore, the multivariate analysis which included the expressions of RARa, RARβ, RARγ, RXRa, RXRβ and RXRγ and the aforesaid clinical variables was performed using the Cox proportional hazards mode. The score of the expressions of RARs/RXRs from 1 to 3 calculated RARs/RXRs positive, while the score of the expression of RARs/RXRs zero calculated RARs/RXRs negative.…”
Section: Rna Expression Studymentioning
confidence: 99%
“…The incidence of gastric carcinoma is declining, it remains the second leading cause of cancer-related mortality worldwide (Crew and Neugut, 2006) with fiveyear survival in France (32.6%), the USA (26%), China (30.5%), Iran (24%) and Japan (screening: 89.4%, no screening: 66.5%) (Msika et al, 2000;Cunningham et al, 2005;Kunisaki et al, 2006;Deng et al, 2010;Khedmat et al, 2011), by the time of diagnosis, most patients have advanced stages of disease (Deng et al, 2010). Its achievement of locoregional control for advanced disease remains very difficult, despite multimodal therapy, 54% of patients had locoregional recurrence (Gunderson and Sosin, 1982).…”
Section: Introductionmentioning
confidence: 99%
“… 2 Several studies have reported a low survival rates of GC in Iran and other low and middle income countries. 2 , 3 , 4 Clinical parameters, including stage at the diagnosis and appropriate treatment (e.g., extent of lymphadenectomy) are the main prognostic factors in GC; 3 , 4 , 5 however, patients with similar clinical stages may experience different survival rates. 6 Therefore, research for exploring new diagnostic and prognostic factors is still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…GC is more prevalent in North and Northwest of the country and its incidence rate in the northwest is more similar to eastern Asia which considered as hot point regions of GC (Sadjadi et al, 2003;Ferlay et al, 2004). The majority cases of GC are being diagnosed in advanced stages, since it is usually asymptomatic in early stages and when symptoms appear it is in late stages leading to poor prognosis (Khedmat et al, 2011). The five year survival of early GC which is limited to mucosa and sub-mucosa is estimated 85-90%, while it decreases as less as 14% in advanced stages (Nakamura et al, 1992;Khedmat et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The majority cases of GC are being diagnosed in advanced stages, since it is usually asymptomatic in early stages and when symptoms appear it is in late stages leading to poor prognosis (Khedmat et al, 2011). The five year survival of early GC which is limited to mucosa and sub-mucosa is estimated 85-90%, while it decreases as less as 14% in advanced stages (Nakamura et al, 1992;Khedmat et al, 2011). The beneficial effectiveness of screening programs has been confirmed in its endemic regions.…”
Section: Introductionmentioning
confidence: 99%